The abel prize. 2003-2007 the first five years (2009)
The Abel Prize. 2003-2007 The First Five YearsHelge Holden, Ragni Piene (eds.)Springer, Berlin, 2010327 paginas. 46 fotografas. 1 DVD con cinco entrevistas.